Causal Genetic Variants in Stillbirth. Issue 1 (24th March 2021) - Stanley, K.E.; Giordano, J.; Thorsten, V.; Buchovecky, C.; Thomas, A.; Ganapathi, M.; Liao, J.; Dharmadhikari, A.V.; Revah‐Politi, A.; Ernst, M.; Lippa, N.; Holmes, H.; et al.
Abstract : ( N Engl J Med . 2020;383:1107–1116) Between 25% and 60% of stillbirth cases are unexplained. Exome sequencing has been used to determine the cause of disease, especially in childhood disorders and fetal structural anomalies. There is an opportunity to further apply clinical exome sequencing to investigating the cause of stillbirth. Previous studies on this topic have been small, concentrated on predetermined causes, and used data from early miscarriages. This study aimed to evaluate the diagnostic utility of clinical exome sequencing in stillbirth using a diverse cohort.